Entrepreneurship Education in Universities: A Review of Current Practices and Future Directions - Marsinah, Marsinah; Umar, Umar; Hatidah, Hatidah; Fitri Indriani, RA; Purwanto, Muhammad Bambang (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the practice of entrepreneurship education in universities and offers insight into the future direction in this field. The study evaluated various approaches and methodologies applied in entrepreneurship education programs at universities worldwide through a comprehensive literature review. The main focus of this study is to identify the latest trends, challenges faced, and opportunities that can be utilized to improve the effectiveness of entrepreneurship education. The review results show that entrepreneurship education programs vary significantly in curriculum, teaching methods, and industry involvement. Some universities have adopted interdisciplinary and practical approaches, including business incubators, mentoring programs, and project-based learning. However, challenges such as lack of resources, teaching quality differences, and program impact assessment limitations still need to be addressed. The research suggests several future directions for entrepreneurship education in universities, including increased collaboration between academics and industry practitioners, integration of digital technologies for more flexible and interactive learning, and better evaluation frameworks to measure learning outcomes and the long-term impact of entrepreneurship programs. This research contributes to the literature by providing insight into how universities can develop and implement more effective entrepreneurship education programs that are relevant to market needs